THE CONCEPT OF “UNORGANIZED YOUTH” AND ITS CHARACTERISTICS - Sharapov B.M. (American Journals Publishing, 2024)
This article reveals the concept of unorganized youth, the specifics of unorganized youth, as well as issues of improving work with unorganized youth.
Keywords: Youth, unorganized youth; crime; antisocial behavior; crime prevention; job.